Physico-chemical parameters and antioxidant activity of baked product fortified with fruit waste powder - Morina, Ariol; Shehaj, Alketa (Journal of Biological Studies, 2022)
Fruit wastes are naturally enriched with vitamins, minerals and other bioactive compounds. Compelling evidences justify and designate peels and relative extracts of numerous fruits as nutraceuticals and functional food. Pomegranate (Punica granatum L.) rind is known as a good source of biologically active food components, and in this paper thepotential use of pomegranate rind powder in cookies was studied. Cookies were produced by substituting 8, 16, 23, 31, and 39% of wheat flour with pomegranate rind powder. Chemical parameters (total acidity, ash, total phenolic and flavonoid content, as well as antioxidant activity (using ABTS method), were evaluated in cookies through the comparison to the control sample with no added pomegranate rind powder. Total ash content increased from 0.65% for cookies S0 (0% PoR) to 1.57% for sample S5 (39% PoR), while moisture content decreased from 6.65% to 4.86% for sample S0 and S5 respectively. Total phenolic content ranged from 294.67 mgGAE/100g to 2180.6 mgGAE/100g and flavonoid content from 118.8 mgCE/100g to 1088 mgCE/100g for S1 (8%) and S5 (39%), respectively. All cookies supplemented with PoR powder exhibited higher total phenolic, flavonoid content, and antioxidant activities compare to control sample.